Profile of thyroid lesions presenting at a tertiary care health centre of North India: 2-year pilot study (2018-2019) - Munjal, Manish; Tuli, Nitika; Rishi, Porshia; Singh, Harjinder; Talwar, Shivam; Sharma, Salony; Munjal, Shubham (International Journal Of Community Medicine And Public Health, 2020)
Background: Diseases of thyroid are of great importance since most of them are amenable to surgical or medical management. Objective of this study was to study the incidence, gender profile, intervention undertaken, fine needle aspiration cytology and histopathological profile of thyroid lesions and correlation of FNAC and HPE studies done after surgical intervention. Methods: This is a prospective study of the patients with thyroid swelling presenting to the head and neck clinic of otorhinolaryngology and head and neck surgery, Dayanand Medical College, Ludhiana over a time period of 2 years (January 2018 to November 2019). All the cases were subjected to a thorough clinical examination followed by evidence-based interventions. Fine needle aspiration cytology was done in all the cases preoperatively as out-patients basis and histopathologically confirmed postoperatively. Results: There were 80/212 subjects presenting in outpatient head and neck clinics of otorhinolaryngology and head and neck services of Dayanand Medical College and Hospital over a period of two years (January 2018 to December 2019). 57 were benign pathologies and 23 malignant. Multinodular goiter was commonest amongst benign (45 cases/78.9%) and papillary carcinoma (19 cases/82.6%) amongst malignant pathologies. Hemithyroidectomy was done in 41 patients (51.2%) while total thyroidectomy was done in 20 patients (25%) while total thyroidectomy with lymph node clearance was done in 19 patients (23.7%). Lymph node involvement was seen in 21.7% (5 cases out of 23 malignant) patients. Fine needle aspiration cytology finding and histopathological examination diagnosis could be corelated in 75 patients (93.75%). Conclusions: Benign lesions are more common than the malignant and amongst malignant papillary carcinoma is the commonest necessitating lymph node clearance.